Rapid way: The determinants for user's intention to use rapid way application in Penang Island - Valizadeh, Iman; Idrus, Rosnah; Ab Rahman Muton, Nursakirah (2013)
Rapid Way Application was developed to help drivers in finding the optimum route using GPS to reach a destination especially if there were any blocked routes/roads caused by accidents, roadwork, natural disaster, etc. This paper presents determinants for user‘s intention to use the Rapid Way Application in Rapid Way Portal.A survey was conducted with 100 respondents to determine the level of user‘s intention to use the application. The analyses of the data were done used correlation and regression analysis.Overall, users‘ intention towards Rapid Way Application was determined directly by the effectiveness of time saving in finding optimum routes as well as users‘ perceived usefulness and ease of use of the application.Cost saving did not seem to be a significant determinant.These indicate that the Rapid Way design must be improved in terms of speed in capturing, processing and deliver the information, be loaded with useful features and must be easy to use with simple navigation.